Glutamatergic transmission associated with locomotion-related neurotoxicity to lindane over generations in Caenorhabditis elegans. (March 2022) - Yu, Yunjiang; Hua, Xin; Chen, Haibo; Wang, Zhengdong; Han, Yajing; Chen, Xichao; Yang, Yue; Xiang, Mingdeng
Abstract: Organochlorine pesticide lindane in the environment and biota results in the potential risks on ecosystem and human health. Lindane can adversely affect the locomotion and nervous system, yet the potential neurotoxicity of lindane over generations remains uncertain. In this study, the neurotoxicity and underlying mechanisms in Caenorhabditis elegans ( C. elegans ) were investigated after parental (P0) exposure to lindane at environmentally relevant concentrations over generations. Exposure to lindane at concentrations of 10–100 ng/L significantly decreased body bends and head thrashes in P0 generation. Significant decrease of fluorescence labeled different neurotransmitters, and clear morphological changes by exposure to lindane at 10–100 ng/L suggested that lindane could induce the neuronal damage in C. elegans . During the transgenerational process, decreased locomotive behaviors were also observed in F1–F3 generations, and head thrashes returned to normal levels in F4 generation. Moreover, lindane exposure down-regulated the expression of dat-1, dop-1, glr-1 and mod-1 genes, while up-regulated unc-30 gene in P0 generation, which recovered to normal levels in F4 generation. Interestingly, eat-4 continued to be regulated from inhibition to stimulation in P0–F4 generations, suggesting that glutamatergic transmission may more contribute to the neurotoxicity of lindane over generations. Graphical abstract: Image 1 Highlights: Neuronal damage was observed following exposure to lindane at 10–100 ng/L. Lindane exposure could transfer its severe neurotoxicity to offsprings. The expression of eat-4 continued to be regulated from P0 to F4 generation. Glutamate transmission may contribute to neurotoxicity of lindane over generations.